2015
DOI: 10.1016/j.cmi.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of Pneumocystis jirovecii pneumonia among Mozambican children <5 years of age admitted to hospital with clinical severe pneumonia

Abstract: We aimed to describe Pneumocystis jirovecii pneumonia (PCP) prevalence and features in children from sub-Saharan Africa and to investigate PCP-associated risk factors. During 2006-2007 we used molecular methods to test children younger than 5 years old admitted with severe pneumonia to a hospital in southern Mozambique for Pneumocystis infection. We recruited 834 children. PCP prevalence was 6.8% and HIV prevalence was 25.7%. The in-hospital and delayed mortality were significantly higher among children with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…In Mozambique, all patients with advanced immunosuppression due to HIV are recommended to receive co-trimoxazole prophylaxis for prevention of PCP. A study by Lanaspa et al in 2015 reported a prevalence of 9.2% of PCP among children <5 years age admitted to hospital with clinical severe pneumonia diagnosed by PCR [ 16 ] ( Table 2 ). Another study in HIV-infected patients with pulmonary infections reported 16.3% of PCP among TB patients [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Mozambique, all patients with advanced immunosuppression due to HIV are recommended to receive co-trimoxazole prophylaxis for prevention of PCP. A study by Lanaspa et al in 2015 reported a prevalence of 9.2% of PCP among children <5 years age admitted to hospital with clinical severe pneumonia diagnosed by PCR [ 16 ] ( Table 2 ). Another study in HIV-infected patients with pulmonary infections reported 16.3% of PCP among TB patients [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of respiratory viruses (influenza virus A and B, respiratory syncytial virus A and B, parainfluenza virus 1, 2, 3 and 4, adenovirus, human rhinovirus, human metapneumovirus, and enterovirus) in nasopharyngeal aspirates (NPA) was determined using four different polymerase chain reactions . Pneumocystis jirovecii infections were investigated in NPA samples using molecular methods . Three specific genes were targeted: (i) mtLSU rRNA locus; (ii) mtSSU rRNA locus; and (iii) DHPS locus .…”
Section: Methodsmentioning
confidence: 99%
“…For instance, when modern diagnostic methods were applied, unsuspected pneumocystis infection was found to be the cause of up to 7% of all severe pneumonia in children younger than 5 years in a hospital in southern Mozambique. 20 In regions with few laboratory facilities, the diagnosis of pneumocystis is often made on clinical grounds. Although such an approach is pragmatic, it lacks specificity, which is necessary to rapidly focus the appropriate antibiotic therapy towards pneumocystis when it is present.…”
Section: Seriesmentioning
confidence: 99%